2009
DOI: 10.3130/aijt.15.453
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Indoor Humidity Environment in Nationally Residential Houses of Japan

Abstract: Based on the energy consumption database of nationally residential houses in various districts of Japan, indoor humidity environment was analyzed. In winter and summer seasons, the statistical values of temperature, relative humidity, absolute humidity and the absolute humidity difference between indoor and outdoor were calculated for each house. In addition, the relations between these statistical values and the level of thermal insulation or airtightness, as well as the possibility of fungal damage were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The Ministry of the environment recommends indoor temperatures of 28°C and 20°C for summer and winter, respectively. The average room temperature and relative humidity in the living room of 12 houses in the Kanto region were 27.3°C/67.0%, respectively, in summer and 17.6°C/48.1%, respectively, in winter 24 . Therefore, the climates of Hong Kong and Japan are quite different.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The Ministry of the environment recommends indoor temperatures of 28°C and 20°C for summer and winter, respectively. The average room temperature and relative humidity in the living room of 12 houses in the Kanto region were 27.3°C/67.0%, respectively, in summer and 17.6°C/48.1%, respectively, in winter 24 . Therefore, the climates of Hong Kong and Japan are quite different.…”
Section: Discussionmentioning
confidence: 83%
“…The average room temperature and relative humidity in the living room of 12 houses in the Kanto region were 27.3°C/67.0%, respectively, in summer and 17.6°C/48.1%, respectively, in winter. 24 Therefore, the climates of Hong Kong and Japan are quite different. However, the room temperature and relative humidity inside houses are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, it was reported that the indoor humidity of houses of Japan was 25% to above 80% throughout the year Zhang et al, 2009 . Thus, the humidity conditions in Trouwborst s experiment are considered to cover those of the general environment.…”
Section: Discussionmentioning
confidence: 99%
“…Als zentrale (auch in der öffent -lichen Diskussion befindliche) Themen sind hierbei Schimmelphäno -mene an Wänden und gesundheitliche Probleme durch künstliche Lüftung zu benennen [34]. Die öko-logischen Probleme eines hohen Energieverbrauches sind hingegen kaum ein Thema, auch wenn diese in Regierungs papieren und Ratingsystemen wie dem japanischen Nach haltig keitslabel CASBEE Beachtung finden [35].…”
Section: Development Of Mould In Contemporary Japanese Residential unclassified